Mathematical modelling of mass transfer in a multi-stage rotating disc contactor column - 506161 Normah Maan (Skudai : Universiti Teknologi Malaysia, 2005)
Thesis (Doktor Falsafah (Fizik) -Universiti Teknologi Malaysia, 2005